To Evaluate the Knowledge and Practice Regarding Home Care Management among Patient on Hemodialysis with Information Education Communication (IEC) Module in Selected Hospitals of Pune City - Elangbam Anibala Devi1 , Manisha Mistry2 , Mangesh Jabade3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Hemodialysis is the medical procedure to remove extra fluid and harmful waste productsfrom blood and to correct electrolyte imbalance of patient whose kidney can no longer do it. It is done usinga hemodialysis machine and dialyzer also called as “artificial kidney. Haemodialysis is one of three renalreplacement therapies. The important role play by the kidneys in the body are in the regulation of bodyelectrolytes; controlling the acid base balance. The primary function of excretory system is to maintainbody’s state of homeostasis by carefully regulating the fluid and electrolytes, removing wastes. Irregularityin the functioning of kidneys and lower urinary tract is common and may occur at any age with varyingdegrees of severity. Dialysis is needed if kidneys no longer remove enough wastes and fluid from your bloodto keep healthy.Purpose and Objective: The purpose of the study was to evaluate effectiveness of information educationcommunication module on knowledge and practice regarding home care management among patient onhemodialysis. 1. To assesses the level of knowledge and practice of hemodialysis patient regarding homecare management. 2. To evaluate the effectiveness of information education communication (IEC) moduleregarding home care management of hemodialysis patient. 3. To associate the knowledge and practice ofpatient on hemodialysis regarding home care management with the selected demographic variables.Methodology: A quasi-experimental non-randomized pre-post-test control group design was used involving40 patients of haemodialysis with AV fistula. After obtaining informed and written consent from the patient,samples were selected using Non-Probability Purposive sampling technique and allocated into two groups of20 patients each in experimental and control group. Self-Structured questioner was used for data collection.The data was analysed by using descriptive and inferential statistics. The statistics used were frequency,mean, percentage, standard deviation and Fishers exact statistic.Results: The descriptive analysis was done to evaluate effectiveness of information education communicationon knowledge and practice regarding home care management among patient on hemodialysis which showsthat information education communication module is effective for enhancement of knowledge and practiceregarding home care management in experimental group than in control group. In experimental group, themean knowledge score was from 8.35(pre-test) to 13.15(post-test) with SD from 1.42(pre-test) to 0.99(posttest) and The mean practice score was from 12.15(pre-test) to 13.8(post-test) with SD from 1.04(pre-test)to 0.52(post-test).The demographic variable for knowledge and practice regarding home care managementamong patient on hemodialysis are not significantly associated.Conclusion: This concluded from the result of the study that information education communication (IEC)module is having significant effect on knowledge and practice regarding home care management. Thedemographic variable for knowledge and practice regarding home care management among patient onhemodialysis are not significantly associated.